Hybrid PEO/sol-gel coatings loaded with Ce for corrosion protection of AA2024-T3 - del Olmo, R. (2023)
Plasma electrolytic oxidation (PEO) has been targeted as an eco-friendly alternative technology to conventional chromic acid anodizing (CAA) for corrosion protection of aluminium alloys in the aircraft industry. However, conventional PEO technology implies high energy consumption. Flash-PEO coatings (≤10 μm) produced in short treatment times (≤ 5 min) constitute a feasible way to overcome this limitation. Nevertheless, the long-term corrosion resistance is compromised, thus requiring novel sealing post-treatments. The present work studies the effect of stand-alone hybrid sol-gel (HSG) and Ce-doped hybrid sol-gel (HSG–Ce) coatings as a sealing posttreatment to evaluate the long-term corrosion resistance of Flash-PEO coatings on aluminium alloy (AA) 2024- T3. The characterization of the PEO, HSG, and HSG-Ce coatings was performed by scanning electron microscopy, X-ray diffraction, water contact angle, dry adhesion tests (ISO 2409), optical profilometry and Fourier transform infrared spectroscopy. The corrosion behaviour was assessed by electrochemical impedance spectroscopy up to 21 days (3.5 wt% NaCl). Active corrosion protection was assessed by immersion tests of artificially scratched coatings. Present findings reveal that low-energy-cost Flash-PEO coatings were successfully formed on AA2024- T3 alloy. Both HSG and HSG-Ce coatings were homogeneously formed on Flash PEO coating. Regarding the corrosion resistance, HSG-Ce showed significant scratch protection during 21 days of immersion in 3.5 wt% NaCl. The results suggest that, while the release of Si and Ce from the coating provided corrosion protection, NO− 3 release promoted localized corrosion phenomena in the scribe. This was associated with the preferential pitting corrosion phenomena at the Cu-rich intermetallic compounds instead of forming a thick and stable NO− 3 - rich passive layer.